AUDIENCE RECEPTION ANALYSIS TOWARD WOMEN’S REPRESENTATION IN DAMSEL - Wardani, Tia Ivanka; Cahyo, Pujo Sakti Nur; Meyrasyawati, Dewi (Rubikon : Journal of Transnational American Studies, 2025)
Upon its release, Damsel's movie became the spotlight since its director, Juan Carlos, claimed it represented contemporary feminism. Using the encoding-decoding model of communication by Stuart Hall, this study aims to analyze the representation of women's heroes and how the audiences respond to them. The data collection techniques include interviews, newspaper articles, and observations from the movie itself. From the decoded messages obtained, the findings show that the hegemonic dominant audience agreed that there was a concept of feminism explained through the heroine; however, the negotiated audience found it unrealistic due to the overpowering female characterization, and the oppositional audience found that the movie depicted women’s suffering due to the patriarchal system rather than women's empowerment. Furthermore, the majority of audience responses indicate agreement where they acknowledge the feminist values in the film. Therefore, this movie stands out among many hero-centric films by highlighting a fresh portrayal of women in media, challenging the conventional depiction of women as weak and needing rescue by men for happiness or salvation. It also questions how well they align with real-world realities.